Blue rubber bleb nevus syndrome with knee joint disorder. Issue 8 (26th April 2016) - Doi, Takehiko; Masumoto, Natsuko; Sonoda, Motoshi; Nakayama, Hideki; Mizuno, Yuji
Abstract: Blue rubber bleb nevus syndrome (BRBNS) involves cutaneous vascular malformation characterized by multiple venous malformations. This commonly affects the skin and gastrointestinal tract. BRBNS is associated with anemia and occasionally involves orthopedic manifestations. A 6‐year‐old boy was referred to hospital for evaluation of anemia. He presented with a rubber‐like soft‐tissue mass in the left knee and the right side of the neck, recurrent pain, and fixed flexion contracture of the knee. Blood examination indicated consumption coagulopathy and anemia caused by not only iron‐deficiency anemia but also microangiopathy. Endoscopy of the gastrointestinal tract indicated multiple bluish‐black sessile venous malformations. Ultrasonography and magnetic resonance imaging of the knee showed intra‐articular and intramuscular involvement. Based on these findings, BRBNS with knee joint disorder was diagnosed. With regard to vascular malformations, like other diseases such as inflammatory arthropathy, ultrasonography of the joint may become a new diagnostic approach for evaluating orthopedic manifestations.